Distinct Gut Microbiota Structure and Function of Children with Idiopathic Central and Peripheral Precocious Puberty - Congfu Huang; Haiying Liu; Wei Yang; Yinhu Li; Bin Wu; Junru Chen; Zhenyu Yang; Cuifang Liao; Limei Liu; Xiaowei Zhang (International Journal of Endocrinology)
Precocious puberty (PP) is one of the most common endocrine diseases in children, and the pathogenesis is currently unknown. Recent studies on the gut-brain axis have shown that there is a correlation between childhood endocrine diseases and the gut microbiota (GM). To explore the GM characteristics of children with different types of PP, we recruited 27 idiopathic central precocious puberty children (ICPP group), 18 peripheral precocious puberty children (PPP group), and 23 healthy children of the same age (HC group). Their stool samples were subjected to 16S rDNA sequencing. In this study, we found that the OTUs numbers, the annotated genera, and α-diversity of GM of the ICPP and PPP group were all significantly higher than that in the HC group (P<0.05). The abundance of butyrate-producing bacteria Prevotella, Lachnospiracea incertae sedis, Roseburia, Ruminococcus, and Alistipes was significantly higher in the ICPP group and the PPP group, and Bacteroides and Faecalibacterium showed significantly higher abundance in the HC group. The GM symbiosis network showed that both Bacteroides and Faecalibacterium were negatively correlated with these butyrate-producing bacteria. The abundances of most significantly changed genera were gradually increased from HC to PPP, and to the ICPP group, while only Bacteroides was gradually decreased. After the prediction of the metabolic pathways of the GM, the cell motility, signal transduction, and environmental adaptation were significantly enriched in the ICPP and the PPP groups (P<0.05), while the carbohydrate metabolism pathway was significantly lower (P<0.001). Overall, this study showed that the GM composition and predicted functional pattern of children with ICPP and PPP are different from healthy children, and PPP may be a transitional stage between ICPP and HC children, which provide a theoretical basis for clinical intervention based on GM in the treatment of PP.